The Experiences of Self-Extension, Archetypes, and Motivations in MMORPG Online Games: An Analysis of Brazilian World of Warcraft Context - João Paulo Nascimento Silva; Frederico Azevedo Alvim Assis; Gabriel Pedrosa; André Grützmann; Daniel Carvalho de Rezende (BAR: Brazilian Administration Review)
Objective: the relationship between player and character is important to understand the concept of the extended self in virtual markets. This study aims to further understand this relationship between player and online game. MMORPGs have several resources that affect the psychological experience of players, who feel connected to their characters. The online world seems to free us from our physical bodies and provide new ways to express ourselves. Thus, the archetypal structures are part of the social imaginary, as fictional universes and avatars in online games. Methods: a netnography methodology was used in order to participate in an online community of the game and collect information about the construction of the game archetype, the players’ relationships and their extended self, and the motivations that engage the players. Results: it was found that archetypes serve as limitations but also as a guarantee of involvement and satisfaction. We also identified person-building relationships in search of an ideal reality, and we found that the motivations that most drive players are the search for relationships and escapism as a way to immerse and escape from ‘real reality.’ Conclusions: the study was directed toward the archetypal construction of the game. The extended self is a form of consumption and interaction with the avatar but also an escape from ‘real reality’ and the co-construction of an archetype of a virtual fantasy world that forms part of the relationship and evolution of consumption and entertainment patterns.